PENGARUH KOHESIFITAS KELOMPOK DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS GURU RAUDHATUL ATHFAL (RA) DI KABUPATEN BEKASI - Hanna Fauziyah (Universitas Negeri Jakarta, 2016)
This research is aimed to investigate the influence of (1) group cohesiveness, (2) job satisfaction, (3) productivity of teachers the raudhatul athfal (kindergarten) school in the district of Bekasi. This research uses causal survey method by using Path Analysis Technicque. This study uses sample from 133 teachers in 20 raudhatul athfal (kindergarten) schools in the district of Bekasi region who are selected by using Slovin formula. The result of the study reveals that: first, there is a positive effect between group cohesiveness and productivity teachers in school. Second, there is a positive effect between job satisfaction and productivity teachers in school. Third, there is a positive effect between group cohesiveness and job satisfaction teachers in school.